Questionnaire to Survey Cosmetic Outcomes in Laparoscopic Surgery for Colorectal Cancer - Masaaki Miyo, MD, PhD; Ichiro Takemasa, MD, PhD; Koichi Okuya, MD, PhD; Tatsuya Ito, MD, PhD; Emi Akizuki, MD, PhD; Tadashi Ogawa, MD, PhD; Ai Noda, MD; Masayuki Ishii, MD, PhD; Ryo Miura, MD; Momoko Ichihara, MD; Maho Toyota, MD; Akina Kimura, MD; et al. (Annals of Surgery Open)
Background and objectives:. There has been a steady increase in the use of minimally invasive surgery, including conventional multiport laparoscopic surgery (MLS) and single-site laparoscopic surgery (SLS) for colorectal cancer. We aimed to evaluate how important the cosmetic outcome, one of the advantages of SLS, is to patients and whether SLS reflects social needs. Methods:. We used a web-based questionnaire to survey nonmedical and medical workers for what factors were considered on the assumption that respondents undergo colorectal cancer surgery and that the most important person for them undergoes. Five items (curability, safety, pain, length of hospital stay, and cosmetic outcomes) were compared. After paired photographs before and after SLS and MLS were shown, perceptions of body image and cosmesis were assessed using a visual analog scale. Results:. This study included a total of 1352 respondents (990 nonmedical and 362 medical). Curability had the highest score (49.9–53.7 points), followed by safety (23.8–24.7 points). The scores for cosmetic outcomes (6.2–7.1 points) were almost equal to those of the length of hospital stay (6.2–7.1 points), which was associated with medical costs and pain (10.0–11.1 points), one of the main reasons for fear of surgery. Participants who were female, younger, and in the nonmedical group placed great importance on cosmetic outcomes. For all questions regarding body image and cosmesis, SLS had superior scores compared with MLS. Conclusions:. Understandably, curability, and safety were most important in colorectal cancer surgery. However, medical workers should consider cosmetic outcomes, even in malignant cases.